1980
DOI: 10.1104/pp.65.3.537
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Promotes Both Volume Flow and Ion Release to the Xylem in Sunflower Roots

Abstract: The effect of abscisic acid (ABA) on the exudation process in excised sunflower root was investigated. A promotion of both ion flux and volume exudation rate was observed. Cutting off the external supply of ions to the roots markedly increased the magnitude of the ABA effect. The promotive effect of ABA on exudation rate was extremely rapid (less than 6 minutes) and seemed to be biphasic. Reasons are given for relating the ABA effect to two separate actions, namely: (a) on water permeability, and (b) on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 15 publications
4
38
0
Order By: Relevance
“…Mean osmolarities of the hydroponic media in the two experiments were 54.1 and 52.0 mOsm. Lp r was calculated as (Glinka, 1980):…”
Section: Measurement Of Lp Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean osmolarities of the hydroponic media in the two experiments were 54.1 and 52.0 mOsm. Lp r was calculated as (Glinka, 1980):…”
Section: Measurement Of Lp Rmentioning
confidence: 99%
“…Exogenously applied ABA is known to increase root hydraulic conductivity (Lp r ) both at the organ and the cellular level (Glinka, 1980;Hose et al, 2000), and this is at least partly explained by an up-regulation of aquaporin genes (Zhu et al, 2005). In agreement with this, ABA-deficient mutants are known to have decreased Lp r (Tal and Nevo, 1973).…”
mentioning
confidence: 92%
“…Karmoker and Van Steveninck (14) and Pitman and Wellfare (16) attributed the observed changes in volume flux entirely to changes in ion transport rates. However, Glinka and Reinhold (10) and Glinka (11,12) have concluded that the major change in volume flux is due to a direct effect on the hydraulic conductance of the system.…”
mentioning
confidence: 99%
“…Thus, ABA has been implicated in plant response to environmental stress, and therefore to low temperature stress (Chandler & Robertson, 1994). As with direct effects of temperature, ABA responses have also been ascribed to root hydraulic conductivity (Collins & Morgan, 1980 ;Glinka, 1980 ;Fiscus, 1981 ;Bassirirad & Radin, 1992), ion flow (Karmorker & van Steveninck, 1978 ;Pitman & Wellfare, 1978), or both. Although various species have been used to assess the effect of root-applied ABA on water and ion fluxes, the results have often been contradictory (Andersen & Proebsting, 1984), and little research has been specially devoted to nitrate uptake and transfer.…”
Section: mentioning
confidence: 99%
“…Our results obtained with a pretreatment of exogenous ABA prior to cooling of the root zone of B. rapa are clearly in agreement with most of the results previously obtained. Thus ABA was found to increase root hydraulic conductivity in certain species such as bean (Karmorker & van Steveninck, 1978 ;Pardossi et al, 1992) and maize (Collins & Morgan, 1980), and ion flows in the root of sunflower (Glinka, 1980) and pear tree (Andersen & Proebsting, 1984).…”
Section: mentioning
confidence: 99%